ICON PART-T 2019–International Scientific Tendinopathy Symposium Consensus: recommended standards for reporting participant characteristics in tendinopathy research (PART-T). Issue 11 (13th September 2019) - Rio, Ebonie Kendra; Mc Auliffe, Sean; Kuipers, Irene; Girdwood, Michael; Alfredson, Hakan; Bahr, Roald; Cook, Jill L; Coombes, Brooke; Fu, Siu Ngor; Grimaldi, Alison; de Vos, Robert-Jan; Lewis, Jeremy S; et al.
Abstract : We aimed to establish consensus for reporting recommendations relating to participant characteristics in tendon research. A scoping literature review of tendinopathy studies (Achilles, patellar, hamstring, gluteal and elbow) was followed by an online survey and face-to-face consensus meeting with expert healthcare professionals (HCPs) at the International Scientific Tendon Symposium, Groningen 2018. We reviewed 263 papers to form statements for consensus and invited 30 HCPs from different disciplines and geographical locations; 28 completed the survey and 15 attended the meeting. There was consensus that the following data should be reported for cases and controls: sex, age, standing height, body mass, history of tendinopathy, whether imaging was used to confirm pathology, loading tests, pain location, symptom duration and severity, level of disability, comorbidities, physical activity level, recruitment source and strategies, and medication use history. Standardised reporting of participant characteristics aims to benefit patients and clinicians by guiding researchers in the conduct of their studies. We provide free resources to facilitate researchers adopting our recommendations.